Tobacco Control Policy in the Netherlands Between Economy, Public Health, and Ideology - Willemsen, Marc C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
Governments have known since the 1960s that smoking results in irreversible health damage. This open access book examines why governments have done so little to combat this when they have been aware of the problem and its solutions for decades. What are the strategies and decisions that make a difference, given that policy environments are often not conducive to change? Taking the Netherlands as an example, this book helps to understand the complex policy process at the national level and why it so often appears irrational to us. It is the most sophisticated analysis of tobacco control policy to date, applying insights from political sciences to the field of tobacco control. Marc C. Willemsen is Professor of Tobacco Control Research at the Department of Health Promotion, University of Maastricht, the Netherlands. He started tobacco research in 1989 and has since become a recognised expert in the field of tobacco control. He wrote and contributed to numerous research studies and scientific papers. In addition to his academic work, he gained first hand insights into the policy making process while working for various national tobacco control organisations. .
Chapter 1 Introduction -- Chapter 2 Dutch tobacco control policy from the 1950s to the present -- Chapter 3 The tempo of Dutch tobacco control policy -- Chapter 4 The national policy environment -- Chapter 5 Making tobacco control policy work: rules of the game -- Chapter 6 The international context: EU and WHO -- Chapter 7 Scientific evidence and policy learning -- Chapter 8 Tobacco industry influence -- Chapter 9 The tobacco control coalition -- Chapter 10 Problem identification and agenda setting -- Chapter 11 Conclusions.
Keywords: Political planning; Political science; Executive power; Economic development; Medical policy; Medicine, Preventive; Health promotion; Public Policy; Governance and Government; Executive Politics; Development Studies; Health Policy; Health Promotion and Disease Prevention